Differential effect of body mass index (BMI) on outcomes of patients treated with docetaxel in prostate cancer - An exploratory analysis. (2022) - Verma, Saurav; Arora, Shalabh; Sahoo, Ranjit Kumar; Singh, Prabhjot; Nayak, Brusabhanu; Haresh, KP; Das, Chandan J; Shamim, Shamim A; Kaushal, Seema; Batra, Atul
Highlights: There is conflicting data on effect of docetaxel based on BMI in mCRPC patients. We analysed whether benefit of docetaxel in patients with mCRPC is modified by BMI. There was no effect of BMI on PFS in patients receiving docetaxel. Overweight and obese patients had a longer OS compared with lean patients. Abstract: Objective: : There are contradictory data on differential effect of docetaxel based on BMI in patients with breast and prostate cancer. We performed an exploratory analysis to determine if the benefit of docetaxel in patients with metastatic castration-resistant prostate cancer (mCRPC) is modified by BMI. Methods: : We performed a post ho c analysis of the data retrieved from the ENTHUSE M1C study. BMI (kg/m 2 ) was categorized as: 18.5 to <25 as lean; 25 to <30 as overweight; and ≥30 as obese. Cox regression models were constructed to determine the impact of BMI on progression-free survival (PFS) and overall survival (OS). Results: : A total of 466 patients were eligible for the current analysis. The median PFS was 7.3, 7.7 and 8.4 months (hazard ratio [HR], 0.92; 95% confidence interval [CI], 0.81 to 1.06; P  = 0.261) in lean, overweight and obese patients. The median OS was 16.6, 20.1 and 21.4 months (HR, 0.75; 95% CI, 0.63 to 0.89; P  = 0.002) for lean, overweight and obese patients. After adjusting for baseline and tumor characteristics, there was no association of BMI with PFS (overweight, HR, 0.89; 95% CI, 0.71 to 1.13; P  = 0.353; obese, HR, 0.86; 95% CI, 0.66 to 1.13; P  = 0.277) while overweight (HR, 0.68; 95% CI, 0.51 to 0.89; P  = 0.006) and obese (HR, 0.59; 95% CI, 0.41 to 0.83; P  = 0.003) patients had significantly better OS compared with lean patients. Conclusions: : There was no effect of BMI on PFS in patients with mCRPC receiving docetaxel. Interestingly, overweight and obese patients had a longer OS compared with lean patients, which is in contradiction to a recent study in breast cancer; and warrants further investigation.